The Effectiveness of a Developed Unit in The Arabic Language Textbook for The Enhancement of 21st Century Skills (Journal Of Educational and Psychological Researches, 2023)
Abstract This research aims to develop a unit as part of a sixth-grade Arabic language textbook and measure its effectiveness in the development of twenty-first-century skills of female students. The author adopted the experimental approach with a quasi-experimental design of the pre-post single-group. A list of the major skills was derived from the framework for the 21st-century skills of the mother tongue that was developed by the Partnership for 21st-Century Skills and reviewed and adjusted by some specialists. According to their views, the unit was developed. The study targeted 15 sub-skills falling under three main skills. The results of the study showed the effectiveness of the developed unit in the development of twenty-first-century skills as a whole and of each skill set. Based on the findings, the study recommends that the concerned authorities responsible for development in the Ministry of Education consider developing school textbooks in light of twenty-first-century skills and enriching them in a way that contributes to the development of these skills among students.